Micro: bit in Science Education: A Systematic Review - Quyen, Kieu Thi; Bien, Nguyen Van; Thuan, Nguyen Anh (Jurnal Penelitian dan Pembelajaran IPA, 2023)
Micro: bit was officially released in 2016 and it was used by over one million students in the UK and its use in schools became a part of the curriculum. After being successfully deployed in the UK, Micro: bit was transferred and applied in many countries around the world. This article will present a systematic review on the use of Micro: bit in science education. Micro: bit is a small, programmable device that is gaining popularity in classrooms around the world due to its affordability, ease of use, and versatility. The systematic review aimed to identify the current state of the field, explored the ways in which Micro: bit is being used in science education and identified gaps in the literature. The systematic review included 37 studies that were published between 2012 and 2023. The results show that Micro: bit is being used in a variety of science education contexts, including physics, chemistry, biology, and environmental science. The studies identified several benefits of using Micro: bit in science education, such as improving students' programming and computational thinking skills, enhancing their understanding of scientific concepts, and increasing their motivation and engagement. Moreover, the systematic review also identified several challenges associated with using Micro: bit in science education, such as a lack of teacher training and support, limited access to technology, and the need for more research on its effectiveness. The systematic review concludes with recommendations for future research and implications for practice. Overall, this systematic review highlights the potential of Micro: bit to enhance science education and encourages further exploration of its use.